PRAGMATIC COMPETENCE IN EFL LEARNERS' ORAL COMMUNICATION: SPEECH ACTS, POLITENESS, AND CONTEXTUAL APPROPRIATENESS PATTERNS - Nurmairina Nurmairina; Nila Lestari (SENSEI RESEARCH CENTER, 2024)
Pragmatic competence is very important in oral communication because the learners must know not only the grammar but also how to speak appropriately. However, many EFL learners are still weak in this aspect. This study discusses the pragmatic competence of EFL learners in oral communication. The study used a descriptive qualitative method supported by quantitative data. The data were collected through a pragmatic judgment test, oral role-play, interviews, and observation. The result shows that the pragmatic competence of the learners is in the moderate category. The learners are good in apology and greeting but still weak in refusal and disagreement, and they also use direct expressions too often. It is suggested that pragmatics should be taught in the speaking class.